FACS-Free isolation and purification protocol of mouse prostate epithelial cells for organoid primary culture - Lilianne Frégeau-Proulx; Aurélie Lacouture; Cindy Weidmann; Cynthia Jobin; Étienne Audet-Walsh (MethodsX, 2022)
The prostate is a gland that contributes to men's fertility. It is highly responsive to androgens and is often the site of carcinogenesis, as prostate cancer is the most frequent cancer in men in over a hundred countries. To study the normal prostate, few in vitro models exist, and most of them do not express the androgen receptor (AR). To overcome this issue, prostate epithelial cells can be grown in primary culture ex vivo in 2- and 3-dimensional culture (organoids). However, methods to purify these cells often require flow cytometry, thus necessitating specialized instruments and expertise. Herein, we present a detailed protocol for the harvest, purification, and primary culture of mouse prostate epithelial cells to grow prostate organoids ex vivo. This protocol does not require flow cytometry approaches, facilitating its implementation in most research laboratories, and organoids grown with this protocol are highly responsive to androgens. In summary, we present a new simple method that can be used to grow prostate organoids that recapitulate the androgen response of this gland in vivo.